Menyelisik Kata-kata yang Khas dalam Nyanyian Jemaat - Rasid Rachman (STFT Jakarta, Indonesia, 2022)
The unfamiliar words in the congregational songs evoke my attention to investigate the roots and the hidden meaning of the songs. Without problems, congregations often keep singing the songs, although some words have no clear meaning. How does the meaning of the Bible verses from which the songs originate change to give rise to different impressions and messages? How can one or two words appropriately narrate the majesty of God? How does a one word conversation change its nuance when sung? These things led me to explore some words and investigate them from the original song and translated vocabulary perspective to find a deeper theological meaning. Some impressive words could be more meaningful or more precise. I chose those words and investigated them to get a more profound impression and message. I found that those words are chosen by the composer or translator convey a personal faith experience that impacts the community. In this article I offer the people to take attention on words of songs. They give a deep nuance and meaning for spiritual life.